Ekstraksi dan Uji Stabilitas Zat Warna Alami dari Biji Buah Pinang (Areca catechu L.) sebagai Bahan Pengganti Pewarna Sintetik pada Produk Minuman: Extraction and Stability Test of Natural Dyes from Areca catechu L. as a Substitute for Synthetic Dyes in Beverage Products - St Chadijah; Sari Ningsih; Ummi Zahra; Syarifah Rabiatul Adawiah; Iin Novianty (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Natural dyes are an alternative dye that is not toxic, environmentally, friendly and easily degraded. Therefore, optimizing the use of body coloring sources is carried out. One of the natural dyes released is tannin from betel nuts. Tannins are polar pigments. This study aims to determine the results of natural dyes in betel nuts and find out the durability produced and known organoleptic results. Dyestuff extraction from betel nuts was carried out with 96% ethanol. Testing the color stability of betel nut seedlings was carried out on the effect of pH, temperature and storage time with the method UV-Vis Spectrophotometer. Then the application of betel nut dyes on beverage products was carried out. The results showed that betel fruit produced tannin dyes in brownish red color with an average tannin content of 28.002 mg/L. Dyes stabilized at pH of 6 by heating at 400C and storage for 2 days. The results of organoleptic tests showed that the extract of areca nut powder can be used as a natural dye in beverage products with a level of color, smell and flavor that emits at a concentration of 0.005 g/mL of dyes. Keywords: Extraction, tannin, areca nuts, color stability, organoleptic